Prevalence and Contributing Factors of Low Back Pain among Nurses in Tertiary Level Hospital - Gautam, G.J.; Gurung, L.; Shrestha, N.; Shrestha, P.S.; Neupane, S. (Journal of Gandaki Medical College-Nepal, 2019)
Background: Low back pain is one of the common musculoskeletal health problems that occur most commonly in nurses among all Health workers. Different researches showed that nurses are suffering from low back pain due to many factors. This research was conducted to find the prevalence and contributing factors of low back pain among nurses. Method: The descriptive cross-sectional study was done among 110 nurses by using stratified proportionate random sampling method. Semi structured self-administered questionnaire with single and multiple responses was administered among nurses after taking informed consent. Statistical package for social sciences (SPSS) 20 was used for analysis of data. Descriptive statistic (percentage and frequency) and inferential statistic (chi square) was used for the study. Result: Among 110 nurses, 64.5% were affected from low back pain and prevalence of low back pain of one year and one week was 60% and 20% respectively. The present working area was strongly associated with low back pain (p=0.000). Prolong standing (64.54%), bending and twisting (64.54%), heavy workload (62.72%), working in same positions (58.18%) were perceived factors of low back pain but heavy mental workload had no relationship with low back pain. Taking rest (99.1%), physiotherapy (92.7%) and taking medication (82.7%) were the factors that decreased low back pain. There was increased work restriction (46.4) and less productive and creative (42.7) due to low back pain. Conclusion: More than half of nurses were affected from low back pain. Prolonged standing, physical workload, bending and twisting were main contributing factors. Therefore, it is recommended to maintain proper body mechanics, periodic screening and timely rotation of nurses for the prevention of low back pain.